2019
DOI: 10.3390/e21010084
|View full text |Cite
|
Sign up to set email alerts
|

Desalination Processes’ Efficiency and Future Roadmap

Abstract: For future sustainable seawater desalination, the importance of achieving better energy efficiency of the existing 19,500 commercial-scale desalination plants cannot be over emphasized. The major concern of the desalination industry is the inadequate approach to energy efficiency evaluation of diverse seawater desalination processes by omitting the grade of energy supplied. These conventional approaches would suffice if the efficacy comparison were to be conducted for the same energy input processes. The misco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…Nanofluids support development of sustainable desalination systems as these fluids are acknowledged to overcome the thermodynamic limits which are faced by current existing desalination systems. Shahzad et al [82] developed a standard universal performance ratio-based evaluation method for comparing the different desalination processes. The study showed that merely 2.5-3% of the primary energy is consumed by thermal desalination processes when combined with power plants.…”
Section: Opportunity To Develop Renewable Energy Powered Cost-competimentioning
confidence: 99%
See 1 more Smart Citation
“…Nanofluids support development of sustainable desalination systems as these fluids are acknowledged to overcome the thermodynamic limits which are faced by current existing desalination systems. Shahzad et al [82] developed a standard universal performance ratio-based evaluation method for comparing the different desalination processes. The study showed that merely 2.5-3% of the primary energy is consumed by thermal desalination processes when combined with power plants.…”
Section: Opportunity To Develop Renewable Energy Powered Cost-competimentioning
confidence: 99%
“…The study showed that merely 2.5-3% of the primary energy is consumed by thermal desalination processes when combined with power plants. Moreover, the performance ratio of all the existing desalination technologies was found to be in the limit of 10-14% of the thermodynamic limit which must be ameliorated up to 25-30% of the thermodynamic limit to meet the 2030 sustainability goals [82].…”
Section: Opportunity To Develop Renewable Energy Powered Cost-competimentioning
confidence: 99%
“…Carbon nanostructures have been considered in search of suitable alternatives, but found to be rather brittle and unsuited for membrane applications [7]. There have been calls for atomic-level theoretical investigations [1] and for a paradigm shift [1,8] to achieve serious progress in water desalination.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the costs of water and energy consumption grow [17]. As seawater RO desalination plants turn more complex, the control theory allows the estimation of uncertainties, the determination of risks and safety measures, and the design of robust and reliable control systems [38][39][40].…”
Section: Introductionmentioning
confidence: 99%